Lifelong Impacts of Moderate Prenatal Alcohol Exposure on Neuroimmune Function - Noor, Shahani; Milligan, Erin D. (Frontiers in Immunology, 2018)
In utero alcohol exposure is emerging as a major risk factor for lifelong aberrant neuroimmune function. Fetal alcohol spectrum disorder (FASD) encompasses a range of behavioral and physiological sequelae that may occur throughout life and includes cognitive developmental disabilities as well as disease susceptibility related to aberrant immune and neuroimmune actions. Emerging data from clinical studies and findings from animal models support that very low to moderate levels of fetal alcohol exposure may reprogram the developing central nervous system (CNS) leading to altered neuroimmune and neuroglial signaling during adulthood. In this review, we will focus on the consequences of low to moderate prenatal alcohol exposure (PAE) on neuroimmune interactions during early life and at different stages of adulthood. Data discussed here will include recent studies suggesting that while abnormal immune function is generally minimal under basal conditions, following pathogenic stimuli or trauma, significant alterations in the neuroimmune axis occur. Evidence from published reports will be discussed with a focus on observations that PAE may bias later-life peripheral immune responses toward a proinflammatory phenotype. The propensity for proinflammatory responses to challenges in adulthood may ultimately shape neuron-glial-immune processes suspected to underlie various neuropathological outcomes including chronic pain and cognitive impairment.